Residents' perceptions of their local food environment in socioeconomically diverse neighborhoods: A photovoice study. (1st April 2020) - Gravina, Leyre; Jauregi, Amets; Estebanez, Ainhoa; Fernández-Aedo, Irrintzi; Guenaga, Nahia; Ballesteros-Peña, Sendoa; Díez, Julia; Franco, Manuel
Abstract: The influence of unhealthy food environments on residents' eating behaviors has been previously documented. Yet, socioeconomic differences across areas are less studied. Participatory studies provide relevant knowledge to better inform future nutrition interventions. We conducted a participatory Photovoice project in which residents interpreted the influence of the local food environment on eating behaviors across three neighborhoods of contrasting area-level socioeconomic status (SES) in Bilbao, Spain. From April to July 2017, a total of 23 residents participated in the three Photovoice groups. Each group critically discussed their photographs (N = 110) in groups of 6–9 participants along six group sessions. Through a consensus-building process, participants identified 27 emerging categories choosing finally 39 related photographs, which followed six conceptual main themes characterizing their local food environment: 1) unhealthy eating behaviors, 2) cultural diversity, 3) retail transformation, 4) social relationships, 5) precariousness, and 6) healthy eating. Although high food quality and fresh products may portray a general healthy food environment in all three neighborhoods, participants discussed why some residents still adopt unhealthy eating behaviors characterized by an excessive consumption of alcohol (high-SES area), sugar loaded foods (high- and middle-SES) and fast food (middle and low-SES). This photovoice participatory methodology helps highlighting important similarities and differences regarding food environment perceptions in the whole socioeconomic spectrum of any given city. This type of participatory approach helps guiding local policies and interventions promoting healthier local food environments.